2016
DOI: 10.1038/ncomms10815
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide association scan in admixed Latin Americans identifies loci influencing facial and scalp hair features

Abstract: We report a genome-wide association scan in over 6,000 Latin Americans for features of scalp hair (shape, colour, greying, balding) and facial hair (beard thickness, monobrow, eyebrow thickness). We found 18 signals of association reaching genome-wide significance (P values 5 × 10−8 to 3 × 10−119), including 10 novel associations. These include novel loci for scalp hair shape and balding, and the first reported loci for hair greying, monobrow, eyebrow and beard thickness. A newly identified locus influencing h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
180
2
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(195 citation statements)
references
References 65 publications
7
180
2
6
Order By: Relevance
“…There is a strong and significant correlation between the average estimates of Native American, European, and African genetic ancestry and the frequency of the equivalent perceived ancestry categories reported in population survey data for these territories ( Figure 5): for native ancestry, R = 0.66 (p = 7  10 4 ); for European ancestry, R = 0.92 (p = 2  10 9 ); and for African ancestry, R = 0.96 (p = 4  10 12 ). The correlation between perceived and genetically estimated ancestry is consistent with the fact that physical appearance is partly genetic (1,2,4,82) and likely an important determinant of perception of ancestry. The review of genetic data underpins the interpretation of ancestry perception data in that, globally, variation in Native, European and African ancestry across the Western Hemisphere bears the imprint of the region's colonial history.…”
Section: The Genetic Diversity Of the Americas Geographic Variation Isupporting
confidence: 56%
“…There is a strong and significant correlation between the average estimates of Native American, European, and African genetic ancestry and the frequency of the equivalent perceived ancestry categories reported in population survey data for these territories ( Figure 5): for native ancestry, R = 0.66 (p = 7  10 4 ); for European ancestry, R = 0.92 (p = 2  10 9 ); and for African ancestry, R = 0.96 (p = 4  10 12 ). The correlation between perceived and genetically estimated ancestry is consistent with the fact that physical appearance is partly genetic (1,2,4,82) and likely an important determinant of perception of ancestry. The review of genetic data underpins the interpretation of ancestry perception data in that, globally, variation in Native, European and African ancestry across the Western Hemisphere bears the imprint of the region's colonial history.…”
Section: The Genetic Diversity Of the Americas Geographic Variation Isupporting
confidence: 56%
“…Similarly, a study of different hair types in an admixed Latin American sample also found a 64% of the variance in nurse-rated hair shape, and 74% for beard thickness was due to genetic factors (Adhikari et al, 2016). However, to date, there have been no studies investigating the heritability of objectively measured hair curvature and diameter.…”
mentioning
confidence: 95%
“…[26,35] Moreover, there are several examples where a given mutation is associated with different hair phenotypes (hair diameter, hair shape or hair whitening), depending on the ethnic background. For example, while rs12203592 single-nucleotide polymorphism (SNP) in intron 4 of the interferon regulatory factor 4 (IRF4) was found associated with grey hair in admixed Latin Americans, [30] the same mutation was found associated with blond hair in Europeans. [36] Of note, rs12821256 SNP in regulatory region of KIT ligand gene was also found associated with blond hair in Europeans.…”
Section: Any Clues From Gwas?mentioning
confidence: 99%
“…[23] In addition, a number of gene loci and polymorphisms were found associated with androgenetic alopecia (AGA) [24][25][26] and alopecia areata, [27,28] as well as hair colour and whitening. [29,30] Of note, even though a strong heritability has been demonstrated in AGA, a direct causative link between identified mutations and AGA has not yet been demonstrated, making it difficult to predict the development of AGA from genetic data. [25] This also stands true for female pattern hair loss (FPHL), which does not share any susceptibility locus with AGA except for the AR/EDA2R locus, in the case of early-onset FPHL.…”
Section: Any Clues From Gwas?mentioning
confidence: 99%